Genetics problem solving in high school testing in Kenya: Effects of metacognitive prompting during testing - Aurah, Catherine M; Cassady, Jerrell Craig; McConnell, Tom John (Electronic Journal for Research in Science and Mathematics Education, 2014)
This study investigated the effectiveness of using metacognitive prompts during testing for improving results in a Genetics Problem Solving Test (GPST). The study, a pre-test post-test, control group quasi-experimental design involving 2x2x2 analysis of covariance (ANCOVA) also investigated the moderating effects of gender and school type. A total of 2,138 high school students purposively selected from seventeen high schools in Western province, Kenya, participated in the study using three validated instruments; Biology Ability Test (BAT), Genetics Problem Solving Test (GPST), and Metacognitive Prompting Questionnaire (MPQ). Findings showed that metacognitive prompting (MP) had a significant effect on students’ genetics problem solving ability, F(1, 2137) = 10.909, p < 0.001. The findings also revealed gender differences, with girls outperforming boys on the genetics problem solving test. Furthermore, a significant interaction between metacognitive prompting and school type showed that students in provincial schools benefited from MPs more than students from district schools. This study established a foundation for instructional methods for biology teachers and recommendations are made for implementing metacognitive prompting in a problem-based learning environment in high schools and science teacher education programs in Kenya.
KerkoCite.ItemAlsoKnownAs: 2339240:G5AWLGH3 2405685:6QCF8TS7
Keywords: ⛔ No DOI found

The influence of infrastructure, training, content and communication on the success of NEPAD’S pilot e-Schools in Kenya - Nyagowa, Hesbon O; Ocholla, Dennis N; Mutula, Stephen M (Information Development, 2014)
This study was conducted to evaluate the contribution of four of the seven e-School dimensions to the success of the pilot phase of the New Partnership for Africa’s Development (NEPAD) e-School project in Kenya. The study employed survey research methodology. All six of the NEPAD e-Schools in Kenya were included and the teachers and students in those schools formed the study population. Of the 5,186 students and teachers, a representative sample of 1,508 was selected using probabilistic techniques. Data was collected using observations and a survey questionnaire. It was established that all six of the e-Schools had installed the basic computing facilities required for integrating information and communication technologies (ICT) in teaching and learning; all the e-Schools were observed to have the Very Small Aperture Terminal (VSAT) for Internet access in computer laboratories where a variable number of computers were installed. The ICT infrastructure provided modest communication capabilities. But while teachers received technical (ICT) training, they did not receive training on pedagogies for ICT integration in teaching and learning. We conducted hypothesis testing and confirmed that the four dimensions of E-School Success Model, investigated in the current study, positively contribute towards the success of the e-School. We therefore concluded that ICT infrastructure quality, content and communication quality, training effectiveness and use make considerable contributions to the success of the pilot phase of the NEPAD e-School project in Kenya. We recommend that stakeholders should continue investing in the NEPAD e-School project. Further studies on the impact of the other three dimensions of the e-Schools are recommended.
Sage UK: London, England shortDOI: 10/f6jwcp KerkoCite.ItemAlsoKnownAs: 10.1177/0266666913489698 10/f6jwcp 2339240:92BVGHM8 2405685:E6WWI998 2405685:NHIH8TRB
Keywords: Kenya; New Partnership for Africa’s Development; e-schools

Technology adoption in secondary mathematics teaching in Kenya: An explanatory mixed methods study - Kamau, Leonard Mwathi (Syracuse University, 2014)
KerkoCite.ItemAlsoKnownAs: 2339240:THKYV7MT 2405685:IAYQII5V
Keywords: ⛔ No DOI found

Kenya’s ICT policy in practice: The effectiveness of tablets and e-readers in improving student outcomes - Kibukho, K.; Kwayumba, Dunston; Jepkemei, Evelyn; Piper, Benjamin (2014)
Kenya is investing in information and communication technology (ICT) to improve children’s learning outcomes. However, the literature on ICT is pessimistic about the ability of ICT alone to improve outcomes, and few ICT programs have created the instructional change necessary to increase learning. The Primary Math and Reading (PRIMR) Initiative implemented a randomized controlled trial of three ICT interventions to enhance learning outcomes: tablets for instructional supervisors, tablets for teachers, and e-readers for students.
Publisher: RTI International. P.O. Box 12194, Research Triangle Park, NC 27709-2194. Tel: 919-541-6000; e-mail: publications@rit.org; Web site: http://www.rti.org KerkoCite.ItemAlsoKnownAs: 2339240:WXEI8ABZ 2405685:MJ9ENT2D
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Improving Early-Grade Literacy in East Africa: Experimental Evidence from Kenya and Uganda - Lucas, Adrienne M.; McEwan, Patrick J.; Ngware, Moses; Oketch, Moses (Journal of Policy Analysis and Management, 2014)
Primary school enrollments have increased rapidly in sub-Saharan Africa, spurring concerns about low levels of learning. We analyze field experiments in Kenya and Uganda that assessed whether the Reading to Learn intervention, implemented by the Aga Khan Foundation in both countries, improved early-grade literacy as measured by common assessments. We find that Ugandan literacy (in Lango) increased by 0.2 standard deviations. We find a smaller effect (0.08) on a Swahili literacy test in Kenya. We find no evidence that differential effects are explained by baseline differences across countries in student test scores, classroom attributes, or implementation fidelity. A plausible explanation that cannot be directly tested is differential effective exposure to the literacy treatment in the tested languages. Students in Kenya were tested in Swahili, which is not necessarily the main language of instruction in primary schools, despite official policy.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/pam.21782 shortDOI: 10/gf7gt2 KerkoCite.ItemAlsoKnownAs: 10.1002/pam.21782 10/gf7gt2 2405685:6XBY922E

USAID/Kenya Primary Math and Reading (PRIMR) Initiative: Kisumu Information and Communication Technology (ICT) Intervention. Endline Report. - Piper, B.; Kwayumba, D. (Research Triangle Institute (RTI), 2014)
00000 KerkoCite.ItemAlsoKnownAs: 2129771:ILKMBDCW 2405685:7K6TGAXF

She called, she Googled, she knew: girls' secondary education, interrupted school attendance, and educational use of mobile phones in Nairobi - Zelezny-Green, Ronda (Gender & Development, 2014)
Girls in Kenya commonly face multiple barriers to school attendance. At the same time, mobile phone use is growing throughout the country, and particularly in urban centres including Nairobi. As this technology spreads, the possibility increases of people using mobile phones for their own development purposes, including for education and learning. This article examines mobile phone use by girls at one secondary school in Nairobi, and in particular their attempts to mediate interrupted school attendance using this technology.
Publisher: Routledge _eprint: https://doi.org/10.1080/13552074.2014.889338 shortDOI: 10/ggtsmq KerkoCite.ItemAlsoKnownAs: 10.1080/13552074.2014.889338 10/ggtsmq 2405685:BB3X32QY
Keywords: ICT4D; Kenya; ___working_potential_duplicate; gender; girls' education; international education and development; mobile learning; school attendance

Integrating Information Communication Technology Skills in Preschool Education in Kenya - Kaindio, Mauta; Wagithunu, Margaret (Mediterranean Journal of Social Sciences, 2014)
The study aimed at investigating the preparedness and attitude of ECDE teachers in preschools, and find out the current situation as far as ICT is concerned. The researchers adopted descriptive design. To obtain information on the current status of the ICT on whether there was any significant difference in preschool teachers’ preparedness in terms of age, qualifications, and experience on ICT. 52 preschool teachers were randomly selected and a questionnaire administered to them. The data was analyzed using SPSS computer software. It was clear from the finding that Kenya is not ready to integrate ICT in preschool curriculum, since the physical facilities, electricity, poverty, trained personnel and teachers’ attitudes towards ICT need to be addresses first. DOI: 10.5901/mjss.2014.v5n5p89
KerkoCite.ItemAlsoKnownAs: 10.5901/mjss.2014.v5n5p89 10/gj37hc 2339240:IKPDXNHI 2405685:ZHP6QFFE

Integrating information communication technology skills in Preschool Education in Kenya - Kaindio, M.P.; Wagithunu, M.N. (Mediterranean Journal of Social Sciences, 2014)
The study aimed at investigating the preparedness and attitude of ECDE teachers in preschools, and find out the current situation as far as ICT is concerned. The researchers adopted descriptive design. To obtain information on the current status of the ICT on whether there was any significant difference in preschool teachers' preparedness in terms of age, qualifications, and experience on ICT. 52 preschool teachers were randomly selected and a questionnaire administered to them. The data was analyzed using SPSS computer software. It was clear from the finding that Kenya is not ready to integrate ICT in preschool curriculum, since the physical facilities, electricity, poverty, trained personnel and teachers' attitudes towards ICT need to be addresses first.
KerkoCite.ItemAlsoKnownAs: 10.5901/mjss.2014.v5n5p 2339240:XS6MU4U5 2405685:EEPP4SFL
Keywords: ⚠️ Invalid DOI

She called, she Googled, she knew: Girls' secondary education, interrupted school attendance, and educational use of mobile phones in Nairobi - Zelezny-Green, Ronda (Gender & Development, 2014)
Girls in Kenya commonly face multiple barriers to school attendance. At the same time, mobile phone use is growing throughout the country, and particularly in urban centres including Nairobi. As this technology spreads, the possibility increases of people using mobile phones for their own development purposes, including for education and learning. This article examines mobile phone use by girls at one secondary school in Nairobi, and in particular their attempts to mediate interrupted school attendance using this technology.
17 citations (Crossref) [2024-02-28] Publisher: Routledge _eprint: https://doi.org/10.1080/13552074.2014.889338 KerkoCite.ItemAlsoKnownAs: 10.1080/13552074.2014.889338 2339240:6CUN627D 2405685:CYKZGKP3
Keywords: ICT4D; Kenya; gender; girls' education; international education and development; mobile learning; school attendance; ⛔ No INSPIRE recid found

An Evaluation of the Implementation of Information Technology in Secondary Schools in Kenya - Mbogo, Gracemary; Anne, Onunga; Kirathi, Miriam (Mediterranean Journal of Social Sciences, 2014)
Education is the best legacy a nation can give to her citizens especially the youth. This is because the development of any nation depends on the quality of education of such a nation. While ICT continues to advance in western Asia countries, African countries still experience a lag in its implementation and continues to widen the digital and knowledge divides. In a recent study by Kiptalam et .al (2010), observed that access to ICT facilities is against the ratio of 1:15 students in developed countries. This study was carried out to investigate the extent to which Information Technology has been implemented in secondary schools in Kenya. 30 teachers were sampled out from various counties. A questionnaire was administered to the sample. Descriptive statistics were used to analyze the data. The fidings indicated that most teachers appreciated the need to implement ICT in schools to enhance their effectiveness during the instructional processes. However, most of the teachers had limited ICT skills and rarely used ICT during their teaching. DOI: 10.5901/mjss.2014.v5n5p215
KerkoCite.ItemAlsoKnownAs: 10.5901/mjss.2014.v5n5p215 10/gj37f2 2339240:4AHCXZ5X 2405685:7TLXRA2N

Impact of Information Communication Technology on Education-Kenya - Kirimi, Josephine (Journal of Educational and Social Research, 2014)
Kenya has made remarkable progress putting in place an ICT policy framework and implementation strategy, complete with measurable outcomes and time frames. The process has had the benefit of sound advice from officials and stakeholders and, perhaps more importantly, strong leadership from the office of the permanent Secretary of the Ministry of Education. However, universal implementation is challenging given the lack of resources, national ICT infrastructure, and even electrical supply- particularly in the rural areas. As technology is bound to rule our present and future, it is good to obtain know-how of the technological reforms at the earliest. Children learn faster and can adapt to changes relatively easily. If they are trained during their school years, they have a high chance of becoming experts in technology. Computers can give lovelier explanations to various subjects. The internet is an ocean of information which can be harnessed for the rendition of information in school. The inclusion of technology in the learning process makes learning an enjoyable activity, thus inviting greater interest from the learners. The administration processes, the official procedures of the school can be simplified by the means of technology. School records, the information about all the students and the teachers and other school employees can efficiently be maintained by means of the advanced technology. Thus we see that technology not only benefits the school students but also eases the office work. It makes possible a more effective way of storage and distribution of information. The realization of the importance of technology in schools and its successful implementation is a necessity. The introduction of technology in schools is the means to bridge the long distance between the present and the future. DOI: 10.5901/jesr.2014.v4n1p435
KerkoCite.ItemAlsoKnownAs: 10.5901/jesr.2014.v4n1p435 10/gkm64d 2339240:SVPSUGP3 2405685:FYWRXAAR

Enhancement of Science Performance through Computer Assisted Instruction among Selected Secondary School Learners in Kenya | Dr. Samuel N Jesse - Academia.edu - Jesse, Samuel (2014)
KerkoCite.ItemAlsoKnownAs: 2339240:PZPJ3Y73 2405685:SFD4AHGW

JiFUNzeni: a blended learning approach for sustainable teachers' professional development - Onguko, Brown Bully (Electronic Journal of e-Learning, 2014)
JiFUNzeni blended learning approach is a sustainable approach to provision of professional development (PD) for those in challenging educational contexts. JiFUNzeni approach emphasizes training regional experts to create blended learning content, working with appropriate technology while building content repositories. JiFUNzeni approach was fieldtested though a design-based research intervention conducted in rural western Kenya. The field test included design, development and implementation of a blended learning course for teachers’ professional development utilizing appropriate technologies including tablets powered by solar energy, open educational resources and open source software. One year after the intervention, follow-up interviews were conducted with eight of the ten teachers and two professional development tutors (PDTs) who participated in the research. The findings from the follow-up interviews shared in this paper revealed that: teachers still used cooperative learning and activity-based learning strategies in their teaching. The PDTs on the other hand designed, developed and implemented one other jiFUNzeni blended learning course for twelve teachers in one school in Korogocho slum in Nairobi city. Implementation by PDTs of jiFUNzeni approach confirmed that they had learned through a sustainable way of delivering professional development in challenging educational contexts. The PDTs utilized the instructional design approaches learned through their participation in the research in designing blended learning content, while they also innovated new ways of developing self-study content as an important creative addition to what they had previously learned. Two teenage children participated in digital content development by advising the PDTs on some appropriate ways of applying technology thus, attesting to the fact that digital natives are important reciprocal supporters to digital immigrants and vice versa.
KerkoCite.ItemAlsoKnownAs: 2339240:5SCGRA3U 2339240:M7R5EIZL 2339240:TS6R3E24 2339240:VWE52LMG 2339240:YMBURAH4 2405685:AKXHE6HE 2405685:Q3Y6Z65Z 2405685:U5WZEBXT 2405685:UNATTHSB 2405685:XVE57FFE 2534378:7WCVV8XM 2534378:DW5I8PW4 2534378:T6RRJMGR
Keywords: Blended Learning; Computer Software; Computers; Cooperative Learning; Cooperative learning; Course Content; Design; Disadvantaged Environment; Distance learning; Education–Computer Applications; Educational Technology; Elementary School Teachers; Faculty Development; Foreign Countries; Handheld Devices; Instructional Design; Internet; Interviews; Kenya; Learning Activities; Multimedia Materials; Open Source Technology; Program Development; Qualitative Research; Rural Areas; Self Evaluation (Individuals); Sustainability; Teacher Attitudes; Teaching Methods; Training; __:import:01; __:match:final; __:matched; __:study_id:2096405; ___working_potential_duplicate; __finaldtb; ⛔ No DOI found

Providing access to education in Sub-Saharan countries through Content-Oriented technology - Kiboro, Angelica; Bailey, Sheena; Nair, Mrinay; Salam, Tomisin; Dwhytie, Alex (2014 IEEE Canada International Humanitarian Technology Conference - (IHTC), 2014)
Access to education has been a growing concern for children in developing economies, namely lack of access to quality customized online content in the classroom and at home; lack of tools that make learning fun and effective in key subject areas; and lack of state resources to meet educational demands. The Rumie Initiative was founded to tackle these concerns. It is a non-profit organization bringing educational content to the world's underprivileged children through low-cost technology. The Rumie Initiative's vision is to redefine the way education is provided, and through this, significantly reduce poverty and drive economic development. The primary advantage of The Rumie Initiative over all other educational technology solutions is that its content is specifically tailored to meet the local educational needs and curriculum standards. Utilizing the vast reserves of free online updated educational content available today; these android driven tablets are an affordable and intuitive way to deliver pre-loaded content without the requirement of internet access. Through mass global volunteerism, The Rumie Initiative collaborates with educators in choosing appropriate educational content and distributes content-loaded tablets through local Non-Governmental Organizations, communities and government entities. The Rumie Initiative has started a program of trials around the world and recently received a positive response at a Computer - Based Math Education Summit in New York hosted by UNICEF from November 21st to 22nd 2013. The initiative was first launched in Haiti on 25th October 2013 and has since, been gaining momentum, currently exploring opportunities in Sub-Saharan countries such as Ghana, Kenya, Uganda, Rwanda, Burundi, South Africa and Nigeria. This paper focuses on The Rumie Initiative's unique business model to reach the masses, emphasizing issues relating to the power of volunteer ism, the forging of strategic development partners, and content-oriented technologies in increasing access to education.
ISSN: null KerkoCite.ItemAlsoKnownAs: 10.1109/ihtc.2014.7147542 10/ggn3tg 2339240:5H77UWY6 2405685:XF5UPDR7
Keywords: Blogs; Communities; Education; Internet; Internet access; Monitoring; Organizations; Rumie initiative; Servers; Terminology; authorisation; computer aided instruction; content management; content-oriented technology; curriculum standards; economics; economies; educational content; educational demands; government entities; non-governmental organizations; online content; standards; sub-Saharan countries